Projeto de sistema ecológico de tratamento e uso agrícola de água residuária sanitária no campus leste da UFERSA, Mossoró-RN - Araújo, Ana Beatriz Alves de (Universidade Federal Rural do Semi-Árido, 2018)
There is a growing importance about the reuse of water in the context of sustainable construction. Currently, the increasing demand and the reduction in the supply of quality water is one of the problems that have been affecting mainly large urban populations. In this context, the need for stimuli to practices, programs and policies that help in water conservation appears. The reuse of water is a strategic activity, as well as being an important tool in the integrated management of water resources. In view of the above, regarding the reuse of water, there is the possibility of using sanitary wastewater for irrigation purposes. The objective of this study was to develop an ecological system for the treatment and agricultural use of wastewater in the eastern campus of the Universidade Federal Rural do Semi-Árido (UFERSA), in Mossoró/RN, to mitigate possible environmental impacts caused. In order to achieve this, the design of an ecological system for the treatment and agricultural use of sanitary wastewater was carried out, with the necessary information to prepare the executive project, where it was possible to estimate that in this facility approximately 61 people generate about 3.05 m³ d-1 of treated wastewater; and also dimension the treatment systems; consisting of a septic tank with two chambers, a flooded system constructed with elephantgrass and a solar reactor; as well as to elaborate the memorials of calculation and descriptive, budget, preparation of technical drawings and the assembly of the executive project of the systems.
Monografia
Keywords: Escassez hídrica; Efluentes; Mitigação; Reúso; Legislação ambiental; Water shortage; Effluents; Mitigation; Reuse; Environmental legislation; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA